Relative specialisation of EU regions: an econometric analysis of sectoral gross fixed capital formation - Claudia Stirböck (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper analyses the level of relative specialisation in terms of gross fixed capital formation in EU regions for the period between 1985 and 1994. Controlling for heteroscedasticity and potential endogeneity problems, we get consistent econometric results. Larger market and regional sizes diminish relative investment specialisation while a higher unemployment rate, population density, the fact of being a central region, the distance to the economic centre, and economic liberalisation increase its level. The variation of the specialisation level of one region over time, however, cannot be explained econometrically, it thus might underlie random disturbances.
Keywords: F15; F2; C30; R12; 330; Economic Geography; Regional Economics; Capital Allocation; Panel Data Analysis; Regionale Arbeitsteilung; Internationale Arbeitsteilung; Investition; Branche; Neue ökonomische Geographie; Schätzung; EU-Staaten